RELATED FACTORS WITH BARRIERS TO THE DISCLOSURE OF POSITIVE HIV STATUS OF PARENTS TO THEIR CHILDREN IN MAKASSAR - Fatmah Afrianty Gobel; Fairus Prihatin Idris (Yayasan Pendidikan dan Research Indonesia (YAPRI), 2018)
The presence of HIV / AIDS in the family adversely affects the quality of life of adolescents, exacerbated by poor parenting. In the meantime, generally HIV / AIDS-positive parents are experiencing barriers to disclosing their HIV positive status to their children. The barriers parents often face in expressing their status include fearing that their children will reveal HIV status to others, fearing stigma, and anxiety for their children's emotional or physical health. This study aims to determine factors related to obstacles to disclosure of HIV positive status of parents to children affected by HIV/AIDS in Makassar City, research method used is Cross Sectional study to identify and know factors related to barriers to HIV status disclosure / Positive parents to children affected by HIV / AIDS. The population and samples in this study were PLWHA who had children and joined the YPKDS Care Foundation Foundation (YPKDS), in the guidance of one of the peer support groups (KDS) in Makassar. Sampling is done by purposive sampling, ie only those who meet the predetermined criteria that will be used as research samples. The age of people living with HIV / AIDS is related to the obstacles of disclosure of HIV-positive parents status to children affected by HIV / AIDS in Makassar, where 56.0% of PLHIV in the early adult category prefer not to disclose their status to affected children compared to end-stage PLWHA only 22.0% who did not disclose the status HIV positive to her child with p value of 0.004. Sex, education, employment, duration of HIV are not related to obstacles to disclosure of HIV positive parental status to children affected by HIV / AIDS in Makassar. It is recommended that PLWHA with early adult age learn much from end-to-end HIV-positive adults about how to approach and ways of disclosing HIV positive status to children affected by HIV.